Risk classification as an essential tool in banking risk management - Ševčenko, Galina; Ustinovičius, Leonas; Balcevič, Robert (Technological and Economic Development of Economy, 2004)
The word “risk” usually has a negative meaning ‐ this notion usually contains some meanings about danger, injuries and wastes. It can be understood as a possibility to suffer injuries, to lose salary or that the main aim would require more funds and abilities than usually. Although risk is not acceptable in the bank activities it can not be avoided. Risk is usually found as a negative, hazardous process or condition that causes injuries, loss of funds, when the credits are not paid back, decreasing of resources, payments out of time, and so on. But on the other hand, as the level of risk is lower, chances to get high benefit are also low. So, usually manufacturers try to avoid risks and choose one of several alternative ways that is less risky, although the proportion of the risk level and the incoming funds should be settled. Article in Lithuanian. Rizikos klasifikacija kaip esminis banko rizikos valdymo įrankis First Published Online: 21 Oct 2010